ANALISIS PERTIMBANGAN DIKABULKANNYA PENINJAUAN KEMBALI PADA PERKARA KORUPSI (STUDI PUTUSAN NOMOR: 237/PK/PID.SUS/2020) - Alfalah, Muhammad Faza; Kristiyadi, Kristiyadi (Sebelas Maret University, 2023)
Abstract: This study examines the judges' considerations in the Supreme Court Decision Number 237 PK/Pid.Sus/2020 where in the decision the supreme judge is of the opinion that the request for judicial review on behalf of Fahmi Darmawansyah can be accepted so that, in his decision the supreme judge imposes a sentence with reduced circumstances verdict previously handed down by a court of first instance. This research is a normative legal research that is prespective and applied with case studies. The technique of collecting primary and secondary legal materials used in this research is by studying laws, documents, and library materials. The results of this study show that the Supreme Court Decision Number 237/Pid.Sus/PK/2020 granted the Return Application on behalf of the applicant Fahmi Darmawansyah. The author is of the opinion that the legal considerations of the judges in the Supreme Court Decision Number 237/PK/Pid.Sus/2020, which states that giving a sum of money and goods to the Sukamiskin Headquarters is considered a form of generosity is inappropriate, because the concept of generosity should not be in accordance with the actions that have been committed. conducted by Fahmi Darmawansyah. So it is not appropriate for the judge to grant the convict's request. Moreover, the defendant had previously committed a repeat of a similar crime.Keywords: Judge's Consideration, Criminal Corruption, Bribery, Judicial Review